Physicochemical Characteristics, Stability, and Irritability of Nanostructured Lipid Carrier System Stabilized with Different Surfactant Ratios - Dyah Rahmasari; Noorma Rosita; Widji Soeratri (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: One of the vital variables affecting the stability and the characteristics of the Nanostructured Lipid Carrier (NLC) is the surfactant concentration. Using the two combinations of surfactants can cause higher stability and a better characteristic of NLC. Tween 80 and Span 20 are anionic surfactants whose combination has not been studied for use in NLC systems. Objective: Determine the effect of different surfactant ratios of Tween 80 and Span 20 on the physicochemical characteristics, stability, and irritability of NLC using the High Shear Homogenization (HSH) method. Methods: Four different surfactant ratios were used in the NLC formulation, in which the ratio of Tween 80:Span 20 were 5:5, 6:6, 7:7, and 8:8, respectively. In this NLC system, cetyl palmitate served as solid lipid, medium-chain triglyceride (CrodamolTM) as liquid lipid, Tween 80, and Span 20 as surfactant components. NLC was characterized for organoleptic, viscosity, pH, zeta potential, particle morphology, particle size, and polydispersity index (PDI), then evaluated for stability using the real-time and freeze-thaw method, and irritability effect. Results: The different ratios of Tween 80 and Span 20 had no significant effect on the particle size, PI, and irritation score of the NLC system. On the other hand, it influenced all formulas' pH value, viscosity, zeta potential, and stability. Conclusions: The different ratios of surfactant combination affect the characteristics and stability of the NLC system.